PENGEMBANGAN VIRTUAL BACKGROUND DENGAN VIDEO MAPPING PROJECTION SEBAGAI INOVASI LAYANAN LABORATORIUM - Rizqi, M Aris; Khairani, Hilda (Poltekkes Kemenkes Bandung, 2025)
The use of technology in the context of education continues to grow along with rapid technological advances. By presenting learning materials in an attractive and interactive visual format, this technology is able to captivate the attention of students and make them more active in the learning process. The purpose of the study was to develop a virtual background with video mapping techniques as an innovation in laboratory services. This research uses R & D research method with sequential exploratory design. The research was conducted in July 2024 at the Laboratory of the Department of Health Promotion, Health Polytechnic of the Ministry of Health Bandung. Qualitative research informants were conducted on 1 video mapping expert and quantitative research samples were conducted on 30 people. The research instrument was carried out validity and reliability to 15 respondents. Qualitative research data collection by means of in-depth interviews with video mapping experts. Quantitative research feasibility test was conducted to 30 users using a questionnaire. Qualitative research results obtained 5 themes namely projector type, lens type, room, lumens, software. Qualitative research user test results obtained 76.44% which means video mapping media is feasible to use. Future research requires similar research to get better technology using LED monitors.